Effectiveness of Single Dose Oral Corticosteroids in Relief of Pain due to Acute Tonsillitis and/or Acute Pharyngitis - Rauniyar, Neeraj; Sah, Santosh Kumar; Tripathi, Prashant (Journal of Institute of Medicine Nepal, 2024)
Introduction Throat pain due to acute tonsillitis and acute pharyngitis hamper with oral intake, speech and swallowing leading to feeling of general weakness and inability to work. The objective of this study was to evaluate the efficacy of single dose of oral corticosteroids for improving or resolving of pain in adults with acute tonsillitis/acute pharyngitis. Methods This study was quasi-experimental study conducted on patients aged 16 years and above with acute tonsillitis/acute pharyngitis were included in the study. A total of 88 patients were included out of which, 46 patients received steroids as a single dose of oral prednisolone (Group A) and in 42 patients, steroids were not used (Group B). Pain score, assessed at 24 hour and 48 hours on Visual Analogue Scale (VAS); and pain duration were compared between two groups. Results There was a male preponderance with male to female ratio of 3:1. Age ranges from 17 to 32 year. The most common symptom was odynophagia presenting in 86 patients out of 88. Pain score at 24 hours was 4.59±0.98 hour in group A and 6.28±1.21 hour in group B (p<0.001). Pain score at 48 hours was 0.41±0.68 hour in group A and 2.98±0.90 hour in group B (p<0.001). Time until onset of pain relief was 3.56±0.98 hour in group A and 5.90±1.08 hour in group B (p<0.001). Time until complete pain relief was 42.61±6.44 hour in group A and 58.71±17.19 hour in group B (p<0.001). Conclusion In adult patients with acute sore throat due to acute tonsillitis and/or acute pharyngitis, single dose of oral prednisolone was effective in reducing pain as well as shortening the duration of pain when compared to the group where it was not used.